Talent Identification and Development in Male Futsal: A Systematic Review - Mendes, Diogo (2022)
This review aimed to identify and synthesize the most significant literature addressing talent identification and development in futsal. A systematic review of Web of Science™ (all databases), Scopus, PubMed and SPORTDiscus databases was performed according to the preferred reporting items for systematic reviews and meta-analyses guidelines. This study included original articles in English, Spanish or Portuguese containing relevant data on talent development/identification of male futsal players. The search yielded 238 articles. After screening, a total of 32 manuscripts were fully reviewed. The quality of the data reviewed was generally good. Results indicate that the most successful players exhibit technical, tactical, anthropometric, physiological and psychological advantages and are distinguished from lower-level players based on their earlier dedication to training. This review highlights the need for those involved in the process of identifying and developing talented futsal players to consider the technical and tactical skills of futsal players, along with their anthropometric and physiological characteristics, scaled to age. Finally, special attention should be paid to the supportive psychosocial environments created in sports academies for developing futsal players. Overall, talent identification and development programmes in futsal need to be dynamic and offer the possibility of changing assessment parameters in the long term.